2021
DOI: 10.3390/ani11010163
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Assessment of Keel Bone Damage in Laying Hens at the Slaughter Line

Abstract: Keel bone damage (KBD) can be found in all commercial laying hen flocks with a wide range of 23% to 69% of hens/flock found to be affected in this study. As KBD may be linked with chronic pain and a decrease in mobility, it is a serious welfare problem. An automatic assessment system at the slaughter line could support the detection of KBD and would have the advantage of being standardized and fast scoring including high sample sizes. A 2MP stereo camera combined with an IDS imaging color camera was used for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 24 publications
(12 reference statements)
2
10
1
Order By: Relevance
“…The differences were only marginal, and the accurate estimation was probably caused by the large sample size. The results are in line with a study by Jung et al [34], who found that optimizations of algorithms led to an improvement in the detection of keel bone damage in automatic assessments. The authors observed that the camera system generally underestimated the presence of keel bone damage.…”
Section: Errors In Assessments Of Reference Surface Area Of Foot Pads...supporting
confidence: 92%
See 1 more Smart Citation
“…The differences were only marginal, and the accurate estimation was probably caused by the large sample size. The results are in line with a study by Jung et al [34], who found that optimizations of algorithms led to an improvement in the detection of keel bone damage in automatic assessments. The authors observed that the camera system generally underestimated the presence of keel bone damage.…”
Section: Errors In Assessments Of Reference Surface Area Of Foot Pads...supporting
confidence: 92%
“…Macro Score 4 was allocated to Macro Score 3, and with the threshold values of 12.66 (original camera score) and 16.68 (updated camera score), these scores were well diagnosable with a sensitivity of 0.82 (original camera score) and 0.81 (updated camera score) and a specificity of 0.80 (original camera score) and 0.87 (updated camera score). Jung et al [34] examined the automatic assessment of keel bone damage using a similar camera system as described in our study. After optimizations of the system, the authors reached a sensitivity of 95% and a specificity of 80% from the previously determined sensitivity of 28% and specificity of 66%.…”
Section: Validation Of Threshold Valuesmentioning
confidence: 99%
“…On the individual test level, the farmers reached mean PABAK values representing substantial to almost perfect agreement. The PABAK means did not differ substantially compared to those reported from reliability tests performed by scientists (using PABAK), for example for keel bone damage in laying hens (Jung et al, 2021); manure on the body of pigs (Wimmler et al, 2021); body condition, lameness, and cleanliness in dairy cows (Wagner et al, 2021); footpad dermatitis in turkeys (Stracke et al, 2020) or broilers (Piller et al, 2020;slightly higher in Louton et al, 2019); and stereotypies, skin lesions, underconditioning, and lameness in sows (Friedrich, 2018). For some of the indicators in our study, the reliability was relatively low and showed potential for improvement by using fewer score levels or modified definitions.…”
Section: Training Successcontrasting
confidence: 56%
“…Additionally, adverse environmental conditions such as poor light and moving animals can impair the recognition of certain findings or distract the assessor on-farm. Some indicators, such as keel bone damage in laying hens (Jung et al, 2021) or underconditioning in sows (Welfare Quality Âź Consortium, 2009b) are commonly assessed by palpation, and some findings might appear differently from the threedimensional view in the two-dimensional pictures. Therefore, a final evaluation of the two methods should additionally take into account an on-farm inter-rater reliability assessment.…”
Section: Training Successmentioning
confidence: 99%
See 1 more Smart Citation